Language attitudes, use, and competences of students of immigrant origin in Catalan secondary education: a moderated mediation model. (4th May 2019) - Ianos, Maria Adelina; Sansó, Clara; Huguet, Àngel; Petreñas, Cristina
Abstract: Following the arrival of a large number of immigrants in Catalonia (Spain), a series of language and educational policies focused on language uses, competences, and attitudes have been implemented with the aim to promote newcomers' social integration and to protect and maintain the regional language, Catalan. This study examines these key factors and how they relate to each other in the case of secondary education students of immigrant origin, also considering their L1 (Spanish or non-Spanish). Specifically, a comparison of the language attitudes, language uses, and competences in Catalan and Spanish of L1 Spanish and L1 non-Spanish participants revealed different patterns between the two groups, largely characterized by a preference for Spanish on the part of the former group. Furthermore, a moderated mediation model is proposed to explain how attitudes influence language competences through language use, as well as how these relationships vary depending on the L1.